(x^2+y^2)^2-2*(x^2-y^2) = 0
una lemniscata di J.Bernoulli;  altre:
(x^2+y^2)^2-2k^2*(x^2-y^2) = 0
(x^2+y^2)^2-2*(x^2-y^2)+4*y^2 = 0
una lemniscata di Booth;  altre:
(x^2+y^2)^2-4k*(x^2-y^2)+4*y^2 = 0
x^4-x^2+y^2 = 0
la lemniscata di Gerono
# Come ottenerle con R
source("http://macosa.dima.unige.it/r.R")
f = function(x,y) (x^2+y^2)^2-2*(x^2-y^2)
PLANE(-1.5,1.5, -1.5,1.5); CURVE(f,"blue")
g = function(x,y) (x^2+y^2)^2-2*(x^2-y^2)+4*y^2
PLANE(-1.5,1.5, -1.5,1.5); CURVE(g,"blue")
h = function(x,y) x^4-x^2+y^2
PLANE(-1.5,1.5, -1.5,1.5); CURVE(h,"blue")

altro